Harmonized human biomonitoring in European children, teenagers and adults - Govarts, Eva (2023)
Funding Information: The authors would like to thank everybody who contributed to the HBM4EU Aligned Studies: the participating children, teenagers, adults and their families, the fieldworkers that collected the samples and database managers that made the information available to HBM4EU, the HBM4EU project partners, especially those from WP7 for developing all materials supporting the fieldwork, WP9 for organizing the QA/QC scheme under HBM4EU and all laboratories who performed the analytical measurements. We would like to acknowledge Sun Kyoung Jung from the National Institute of Environmental Research of South-Korea for providing the KoNEHS Cycle III results (crt adjusted). HBM4EU is co-financed under Horizon 2020 (grant agreement No 733032). The authors thank all principal investigators of the contributing studies for their participation and contribution to the HBM4EU Aligned Studies and the national program owners for their financial support. Further details on funding for all the participating studies can be found in the Supplemental Material, Table S12.